Finance and Development, December 1975. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1975)
This paper reviews the 1975 Annual Meetings of the Boards of Governors of the IMF and the World Bank that were held in Washington, D.C., from September 1-5. The paper highlights that three separate but related themes dominated the discussion at the Annual Meetings. The first was the need to combat recession without aggravating inflation. The second was the immediate needs of developing countries in the present situation. And the third was the urgency of making further progress toward reform of the international monetary system.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet